Pengembangan Sistem Informasi Terintegrasi Untuk Manajemen Barbershop Berbasis Web Pada Styling House.Co - Ahmad Fikri Fajri; Eka Iswandy (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2026)
The rapid development of information technology has encouraged businesses to implement information systems to improve service quality and operational efficiency, including barbershop businesses. Styling House.Co Barbershop still performs most of its business processes manually, including customer data management, service management, and reservation recording. These manual processes often lead to recording errors, difficulties in retrieving information, and inefficient customer service.This research aims to design and develop a web-based information system for Styling House.Co Barbershop using the CodeIgniter 4 framework and the Waterfall software development methodology. The development stages include requirements analysis, system design using Unified Modeling Language (UML), implementation using PHP, HTML, CSS, JavaScript, and MySQL database, followed by system testing using the Black Box Testing method.The developed system successfully improves customer data management, service management, employee management, online booking, payment processing, and report generation. Furthermore, the system provides customers with easier access to service information and online reservations, resulting in better service quality and more efficient business operations